Gambaran Pembinaan Kegiatan Ekstrakurikuler Olahraga di SMAN 13 Padang - Novrita Aslina Roza; Syuraini Syuraini (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2018)
The research is motivation by the good sports extracurricular at SMAN 13 Padang. This condition is suspected because the guidance provided by the coach in sports extracurricular activities is quite good. This study aims to see an overview of coaching in sports extracurricular activities at SMAN 13 Padang. This research of type quantitative descriptive. Population in this study were eleven-grade students participating in sports extracurricular activities at SMAN 13 Padang as many as 38 people who were all respondents to the study. Data collection techniques using questionnaires by analyzing data using percentage calculations. The results showed that the picture of coaching in sports extracurricular activities at Padang Public High School 13 was good. Suggestions from the results of this study for coaches to maintain and improve the guidance provided in the form of guidance and supervision.Keywords: Extracurricular, Coaching